2021
DOI: 10.1002/msc.1589
|View full text |Cite
|
Sign up to set email alerts
|

The changing pattern of acute spinal referrals during primary and secondary waves of the COVID‐19 pandemic

Abstract: Introduction The COVID‐19 pandemic has had a devastating effect on health systems globally. This led to changes in patient access to healthcare particularly spinal services. This study investigates the impact of the pandemic on the volume of patients being referred to and accessing spinal services during both the first and second waves. Methods All emergency spinal referrals and related hospital attendances to the emergency department in a busy district general hospital were analysed. The data were evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Given the emergent nature of patients with neurological compromise in spinal injury, RT-PCR swab results may not have returned prior to surgery commencement, and therefore COVID-19 protocols must be adhered to. This study showed that neither time to theatre nor mean surgical time was significantly increased between the two cohorts [consistent with the prior literature]; however, time inside the operating theatre was significantly increased, which is most likely due to time required to implement the risk reduction strategies for aerosolising procedures ( 17 , 18 ). Interestingly, these findings are not consistent with operative intervention in general orthopaedic and hand trauma from the same institute, with total surgical time decreasing in both respective pandemic cohorts ( 6 , 7 ).…”
Section: Discussionsupporting
confidence: 87%
“…Given the emergent nature of patients with neurological compromise in spinal injury, RT-PCR swab results may not have returned prior to surgery commencement, and therefore COVID-19 protocols must be adhered to. This study showed that neither time to theatre nor mean surgical time was significantly increased between the two cohorts [consistent with the prior literature]; however, time inside the operating theatre was significantly increased, which is most likely due to time required to implement the risk reduction strategies for aerosolising procedures ( 17 , 18 ). Interestingly, these findings are not consistent with operative intervention in general orthopaedic and hand trauma from the same institute, with total surgical time decreasing in both respective pandemic cohorts ( 6 , 7 ).…”
Section: Discussionsupporting
confidence: 87%